Acineta persiensis sp. n. (Ciliophora, Suctorea) — a New Freshwater Suctorian Species from the Water Mites of the Genus Protzia (Acari, Hydrachnidia) - Dovgal, I.V.; Pesic, V. (Вестник зоологии, 2007)
Acineta persiensis Dovgal et Pesic, sp. n. — a new suctorian ciliate species, was described from specimens collected in Guik stream, Khorrasan Province, Iran and in Stream Bistrica near village Crkvine, Montenegro. The suctorian was found colonizing the legs of the hydrachnid mites Protzia sepasgosariani and P. invalvaris. A new species differs from other species of the genus Acineta in the lorica structure, stalk morphology, the ability to hyperphoretic pseudocolonies formation and geographical distribution.